Oxidative-Signaling in Neural Stem Cell-Mediated Plasticity: Implications for Neurodegenerative Diseases - Mafalda Ferreira dos Santos; Catarina Roxo; Susana Solá (MDPI AG, 2021)
The adult mammalian brain is capable of generating new neurons from existing neural stem cells (NSCs) in a process called adult neurogenesis. This process, which is critical for sustaining cognition and mental health in the mature brain, can be severely hampered with ageing and different neurological disorders. Recently, it is believed that the beneficial effects of NSCs in the injured brain relies not only on their potential to differentiate and integrate into the preexisting network, but also on their secreted molecules. In fact, further insight into adult NSC function is being gained, pointing to these cells as powerful endogenous "factories" that produce and secrete a large range of bioactive molecules with therapeutic properties. Beyond anti-inflammatory, neurogenic and neurotrophic effects, NSC-derived secretome has antioxidant proprieties that prevent mitochondrial dysfunction and rescue recipient cells from oxidative damage. This is particularly important in neurodegenerative contexts, where oxidative stress and mitochondrial dysfunction play a significant role. In this review, we discuss the current knowledge and the therapeutic opportunities of NSC secretome for neurodegenerative diseases with a particular focus on mitochondria and its oxidative state.